Low CD4+ T cell counts are not risk factor for Malassezia species infection in HIV/AIDS patients - Epi Panjaitan; Satiti Retno Pudjiati; Agnes Sri Siswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Human immunodefiiency virus (HIV) infection and aquired immunodeficiency syndrome (AIDS)cause a progressive depletion of CD4+ T cell populations accompanied by progressive impairmentof cellular immunity and increasing susceptibility to opportunistic infections. Seborrheic dermatitisis one of the most common skin opportunistic infections on HIV/AIDS patients. Malasseziaspecies is bilieved as the causative of seborrheic dermatitis. The aim of the study was to evaluatelow CD4+ T cell counts as risk factor for Malassezia sp. infection in HIV/AIDS patients. This wasan observational study with cross-sectional design conducted on HIV/AIDS patients who attendedin Department of Dermatology and Venereology, Faculty of Medicine Universitas Gadjah Mada/Dr Sardjito General Hospital, Yogyakarta and met the inclusion and exclusion criteria. Culture ofMalassezia sp. was conducted in Department of Microbiology and classified as high (>100 CFU/tape) and low (<100 CFU/tape) density colonies. CD4+ T cell counts were measured in Departmentof Clinical Pathology and classified as high (>200 cells/mm3) and low (<200 cells/mm3) CD4+ Tcell counts. A total of 83 subjects with HIV/AIDS comprising 54 (65.1%) males and 29 (34.9%)females aged 20 - >60 years were involved in the study. The number of Malassezia sp. colonyon subjects with high and low CD4+ T cell counts were 31.55 ± 26.21 and 25.2 ± 33.89 CFU/tape, respectively. No significantly relationship between between CD4+ T cell count and Malasseziasp. colony number was observed in the study (p=0.607; 95%CI=0.04-5.19; RP=0.452). Inconclusion, low CD4+ T cell counts is not risk factor for Malassezia sp. infection in HIV/AIDSpatients.